CLINICAL AND BIOLOGICAL ASPECTS OF HEMATURIA IN CHILDREN - Abazi Emini, Nora; Jordanova, Olivera; Tasic, Velibor; Hasani, Arjeta (Journal of Morphological Sciences, 2022)
Introduction: Hematuria is very common in childhood but if it persists in multiple urine examinations it deserves further detailed evaluation. Hematuria is an increased excretion of erythrocytes in the urine. It can be macroscopic or microscopic. It is a finding of more than 5 erythrocytes/ hpf in the urine sediment.This study aims to analyze demographic and etiological characteristics of hematuria in children, to determine the diagnostic value of urine calcium, proteinuria and ultrasound findings in both forms of hematuria, microscopic and macroscopic. Material and methods: The study includes 150 children aged 1-16 years, with confirmed hematuria in the period January 2020 - February 2022 at the University Children’s Hospital - Skopje. Patients are divided into two groups: the group with macroscopic and the group with microscopic hematuria. The two groups are compared in terms of ultrasound findings, urine calcium and proteinuria. Familial urinary screening for hematuria was also performed. Results: From 150 children 59.33% had microscopic and 40.67% macroscopic hematuria. The most common proven etiology in microscopic hematuria is familial hematuria (34.83%) while in macroscopic hematuria the most common cause is glomerulonephritis (39.34%). Hypercalciuria was found in 5 (6%) of the examined children. Proteinuria is significantly higher in the gross hematuria group. Of the 80 screened families, 35 found a familial form of hematuria. Conclusion: This study indicates the frequency of familial hematuria and the importance of familial screening. The values of urine calcium and ultrasound finding do not have a statistically significant difference between the two groups while proteinuria is higher in macroscopic hematuria (p <0.05). Key words: hematuria, macroscopic, microscopic, children.